2004
DOI: 10.2337/diabetes.53.10.2691
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1 Concentration Is Genetically Correlated With Insulin Resistance, Obesity, and HDL Concentration in Mexican Americans

Abstract: The metabolic syndrome and type 2 diabetes are associated with endothelial activation (and thus with inflammatory processes leading to atherosclerosis), but the mechanisms that underlie these associations are not fully understood. Endothelial intercellular adhesion molecule (ICAM)-1 plays an important role in the recruitment of immune cells during the development of atherosclerotic plaque and is a marker of inflammatory disease. We performed bivariate quantitative genetic analyses to estimate genetic and envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
7
42
1
Order By: Relevance
“…Soluble forms of ICAM1 and VCAM1 have been found to enter the systemic circulation, as a result of proteolytic cleavage at the cell surface, releasing the extracellular domain. Indeed, sICAM1 and sVCAM1 levels are higher in insulin resistance, obesity and type 2 diabetes (Guler et al 2002, Leinonen et al 2003, Kent et al 2004. There is also evidence indicating that women with GDM develop endothelial dysfunction during pregnancy (Knock et al 1997), and despite returning to NGT, endothelial dysfunction is still evident in women 1-year post GDM pregnancy (Pleiner et al 2007).…”
Section: Figurementioning
confidence: 88%
“…Soluble forms of ICAM1 and VCAM1 have been found to enter the systemic circulation, as a result of proteolytic cleavage at the cell surface, releasing the extracellular domain. Indeed, sICAM1 and sVCAM1 levels are higher in insulin resistance, obesity and type 2 diabetes (Guler et al 2002, Leinonen et al 2003, Kent et al 2004. There is also evidence indicating that women with GDM develop endothelial dysfunction during pregnancy (Knock et al 1997), and despite returning to NGT, endothelial dysfunction is still evident in women 1-year post GDM pregnancy (Pleiner et al 2007).…”
Section: Figurementioning
confidence: 88%
“…Inflammation of the vascular wall causes endothelial cells to express a wide variety of endothelial adhesion molecules, including intracellular adhesion molecule-1. sICAM-1 can be regarded as a marker of both endothelial function and inflammation (11) that is associated with atherosclerotic progression (44) and its levels are increased in obesity (9,(14)(15)(16)(17)19). It has been suggested that sICAM-1 mediated endothelial dysfunction is stimulated by cytokines secreted by adipose tissue (45).…”
Section: All Data Are Presented As the Mean ± S Bmi Body Mass Indexmentioning
confidence: 99%
“…Disturbed endothelial function can be assessed by measuring the level of these molecules. The concentration of soluble intracellular adhesion molecule-1 (sICAM1) and plasminogen activator inhibitor 1 (PAI-1) have been shown to be the earliest markers of endothelial dysfunction (6,7) and there is evidence that these substances are increased in obese patients (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in human UBL5 are associated with variation in body composition; blood levels of total cholesterol, LDL, and triglycerides; and insulin response to glucose challenge [23]. Given the correlation between inflammation and the metabolic syndrome [6,9] it is interesting to note that the Chr. 19 QTL coincides with genes related to dyslipidemia, hypertension, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study [9] we found that sICAM-1 levels are genetically correlated with several measures of obesity and insulin resistance in a Mexican American population with elevated prevalence of obesity and T2DM: the San Antonio Family Heart Study (SAFHS, [10]). This finding provides suggestive evidence for the existence of common genetic factors underlying development of obesity, T2DM, and inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%